Fine-scale assessment of Chlorella syrup as a nutritional supplement for honey bee colonies - Dostálková, Silvie; Kodrík, Dalibor; Simone-Finstrom, Michael; Petřivalský, Marek; Danihlík, Jiří (Frontiers in Ecology and Evolution, 2022)
Malnutrition plays a remarkable role in honey bee colony losses. As a result of global agriculture, the availability of food sources for bees, especially pollen and nectar, declines. The solution to inadequate natural sources is the additional feeding of honey bee colonies with food supplements. The algae Chlorella is a natural food source, with a nutrient profile similar to natural pollen, thus it has promising application in beekeeping. We evaluated Chlorella vulgaris syrup as a dietary supplement in the view of the oxidative stress that may be caused by long term administration to the colonies. Consuming Chlorella syrup did not influence the activity of digestive enzymes of summer honey bee workers, however, lipase activity slightly increased. After Chlorella application to colonies, we observed higher gene expression of antioxidant enzymes catalase and superoxiddismutase1 in adult workers; however, in larvae the expression of those genes was not affected. Surprisingly, the gene expression did not correspond with enzyme activity in adult bee abdomens. In Chlorella fed colonies, we recorded a higher concentration of vitellogenin, which plays multiple roles in honey bee physiology, i.e. antioxidant, storage protein, or immunity-related functions. Our new findings brought evidence that Chlorella did not negatively affect the digestion or oxidative balance of honey bees, thus its application as a pollen supplement can be fully recommended for maintaining the health of honey bee colonies during periods of dearth.